PERLUASAN AREAL PEMASARAN MINUMAN INSTAN VITEPLUS PRODUKSI UD MAJU JAYA SUMENEP - Ismawati, Ismawati; Wibisono, Aryo; Yuniastri, Ratih (Jurnal Terapan Abdimas, 2021)
Abstract. Partners in PKM activities is UD Maju Jaya with the product soursop leaf instans drink  called viteplus. Viteplus is a instan drink from powder product made from sugar which is formulated with soursop leaf exstract and traditional herbal ingredients. In  running a business, partners have been able to increase production capacity. Increasing production capacity also needs to be supported by increased marketing so that businesses can continue to run and be profitable. Through PKM activities, the team provides assistance to partners in solving problems faced, namely increasing marketing. Marketing increase is measured based on the product marketing area. Activities carried out as an effort to provide solutions to partners, namely training, mentoring and monitoring. The results of PKM activities indicate an increase in the product marketing area of> 50%, where before the activity the product was only marketed in 3 districts and after PKM activities increased the marketing area to 5 districts, namely Gapura, Sumenep City District, Bluto, Ganding and Guluk - Guluk. Abstrak. Mitra dalam kegiatan PKM adalah UD Maju Jaya denga n produk minuman instan daun sirsak dengan nama produk viteplus. Viteplus merupakan produk yang minuman dalam bentuk bubuk yang terbuat dari gula pasir yang diformulasi dengan sari daun sirsak dan bahan jamu tradisional. Dalam menjalankan usaha, mitra telah mampu mennigkatkan kapasitas produksi. Peningkatan kapasitas produksi perlu didukung juga oleh peningkatan pemasaran agar usaha dapat terus berjalan dan profitable. Melalui kegiatan PKM tim melakukan pendampingan terhadap mitra dalam menyelesaikan permsalahan yang dihadapi yaitu peningkatan pemasaran. Peningkatan peasaran diukur  berdasarkan areal pemasaran produk. Kegiatan yang dilakukan sebagai upaya memberikan solusi terhadap mitra yaitu pelatihan, pendampingan dan monitoring. Hasil kegiatan PKM menunjukkan adanya peningkatan areal pemasaran produk >50%, dimana sebelum kegiatan produk hanya dipasarkan di 3 kecamatan dan setelah kegiatan PKM meningkat areal pemasarannya menjadi 5 kecamatan antara lain Gapura, Kecamatan Kota Sumenep, Bluto, Ganding dan Guluk – Guluk.